2009
DOI: 10.1002/chem.200901448
|View full text |Cite
|
Sign up to set email alerts
|

Structural Variations and Molecular Dynamics of Rare‐Earth Metal Complexes with the N,N‐Bis(2‐{pyrid‐2‐yl}ethyl)hydroxylaminato Ligand

Abstract: The reaction of the donor-functionalised N,N-bis(2-{pyrid-2-yl}ethyl)hydroxylamine and [LnCp3] (Cp=cyclopentadiene) resulted in the formation of bis(cyclopentadienyl) hydroxylaminato rare-earth metal complexes of the general constitution [Ln(C5H5)2{ON(C2H4-o-Py)2}] (Py=pyridyl) with Ln=Lu (1), Y (2), Ho (3), Sm (4), Nd (5), Pr (6), La (7). These compounds were characterised by elemental analysis, mass spectrometry, NMR spectroscopy (for compounds 1, 2, 4 and 7) and single-crystal X-ray diffraction experiments.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
2
15
1
Order By: Relevance
“…The singlet of the protons of GaMe 3 does not split into different signals, indicating that the gallium atom remains bonded to the hydroxylaminato oxygen atom during the exchange process. Compared to the spectra of the EMe 3 -free [YCp 2 ON(C 2 H 4 -oPy) 2 ] [14] (Type A) the coordination of the EMe 3 -units to the ligand oxygen atom effects a simplification of the dynamic, because in this case solely the pyridyl exchange process and no further splitting is observed. By means of the Eyring equation it is possible to estimate the activation energy of this exchange process for 2 to be 44 kJ mol -1 .…”
Section: Molecular Dynamics Of the Compounds 1-17mentioning
confidence: 91%
See 4 more Smart Citations
“…The singlet of the protons of GaMe 3 does not split into different signals, indicating that the gallium atom remains bonded to the hydroxylaminato oxygen atom during the exchange process. Compared to the spectra of the EMe 3 -free [YCp 2 ON(C 2 H 4 -oPy) 2 ] [14] (Type A) the coordination of the EMe 3 -units to the ligand oxygen atom effects a simplification of the dynamic, because in this case solely the pyridyl exchange process and no further splitting is observed. By means of the Eyring equation it is possible to estimate the activation energy of this exchange process for 2 to be 44 kJ mol -1 .…”
Section: Molecular Dynamics Of the Compounds 1-17mentioning
confidence: 91%
“…[14] These processes lead to very complex VT-NMR spectra and we found that besides an exchange of the pyridyl groups, further dynamic processes take place.…”
Section: Molecular Dynamics Of the Compounds 1-17mentioning
confidence: 97%
See 3 more Smart Citations